2015
DOI: 10.1097/qai.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Prescription of Opioids and/or Benzodiazepines and Mortality Among HIV-Infected and Uninfected Patients

Abstract: Background Increased long-term prescribing of opioids and/or benzodiazepines necessitates evaluating risks associated with their receipt. We sought to evaluate the association between long-term opioids and/or benzodiazepines and mortality in HIV-infected patients receiving antiretroviral therapy and uninfected patients. Methods Prospective analysis of all-cause mortality using multivariable methods and propensity score matching among HIV-infected patients receiving antiretroviral therapy and uninfected patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 74 publications
3
49
1
Order By: Relevance
“…Further, we found those with anxiety are likely to be co-prescribed sedating medications such as benzodiazepines as might be expected, and we also found white and female participants had greater odds of co-prescription as compared to non-whites and males. Although numbers of deaths in our cohort were small, our results were consistent with findings from other studies of individuals with HIV(33) and in the general population(14, 21, 34): mortality was higher in participants prescribed chronic opioids, and in individuals co-prescribed opioids and other sedating medications. These findings have important implications for developing interventions to improve safety of opioid prescribing in HIV care.…”
Section: Discussionsupporting
confidence: 91%
“…Further, we found those with anxiety are likely to be co-prescribed sedating medications such as benzodiazepines as might be expected, and we also found white and female participants had greater odds of co-prescription as compared to non-whites and males. Although numbers of deaths in our cohort were small, our results were consistent with findings from other studies of individuals with HIV(33) and in the general population(14, 21, 34): mortality was higher in participants prescribed chronic opioids, and in individuals co-prescribed opioids and other sedating medications. These findings have important implications for developing interventions to improve safety of opioid prescribing in HIV care.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, as patients with HIV live longer, concerns about effects of high-risk medications on geriatric populations who are more prone to falls, fractures, decreased metabolism and altered pharmacodynamics, have increased [21]. Finally, a recent study of long-term opioid receipt demonstrated a higher risk of death among individuals with HIV compared to those without HIV [22]. …”
Section: Introductionmentioning
confidence: 99%
“…There have also been several thousand yearly reported overdoses involving a hypnotic in which an opiate was not involved. So great is the recent increase in overdose and suicide deaths that it has lowered overall life expectancy in much of the U.S. adult population 7,8 . Overdoses kill more Americans than automobile accidents or murders.…”
Section: Introductionmentioning
confidence: 99%